Complications Are Rare From Middle Turbinate Resection: A Prospective Case Series. Issue 6 (November 2019) - Pinther, Steven; Deeb, Robert; Peterson, Edward L.; Standring, Robert T.; Craig, John R.
Background: When chronic rhinosinusitis with nasal polyps (CRSwNP) fails to respond to medical therapy, endoscopic sinus surgery (ESS) plays an integral role in management. Some studies have shown that middle turbinate resection (MTR) during ESS leads to decreased polyp recurrence and revision ESS rates. Other studies suggest MTR can lead to complications. Objective: The purpose of this study was to assess the safety of MTR during ESS for CRSwNP by determining the incidences of intraoperative cerebrospinal fluid (CSF) leak, postoperative epistaxis requiring operative intervention, and postoperative complete frontal stenosis. Methods: A multiinstitutional, prospective case series of 91 adult CRSwNP patients was conducted. Patients with medically refractory CRSwNP underwent primary or revision ESS plus MTR by 3 surgeons. Two of the surgeons performed partial MTRs, and one of the surgeons performed complete MTRs. Patients were evaluated for the following complications: intraoperative CSF leak during MTR, postoperative epistaxis requiring operative intervention, and postoperative complete frontal ostial stenosis. Secondary outcomes included changes from preoperative to postoperative 22-item Sinonasal Outcome Test (SNOT-22) scores and revision ESS rates. Results: Unilateral or bilateral complete ESSs with MTRs were performed on 91 CRSwNP patients. In total, 173 MTRs were performed. Two surgeons performed 97 partial MTRs on 49 patients, and the third surgeon performed 76 complete MTRs on 42 patients. One CSF leak occurred during partial MTR (1/173, 0.57%). No patients suffered postoperative epistaxis requiring operative intervention, and no patients developed complete frontal stenosis. From preoperatively to postoperatively, mean SNOT-22 scores decreased from 53.7 to 13.1 ( P  = .001). No revision ESS was needed during the follow-up period. Mean follow-up time was 7.5 ± 5.4 months. Conclusions: Partial and complete MTR during ESS for CRSwNP in this cohort resulted in very low, acceptable intraoperative and short-term postoperative complication rates and no detriment to SNOT-22 scores.